Pengaruh Penambahan Wijen Sangrai Terhadap Karakteristik Fisikokimia Pada Mayones Vegetarian: The Effect Of Adding Roasted Sesame On The Physicochemical Characteristics Of Vegetarian Mayonnaise - putri, raekhanrahmah; Handayani, Murni; Utami, Sari Widya; kristiningsih, ari (Journal of Sustainable Research In Management of Agroindustry (SURIMI), 2024)
Mayonnaise is a mixture of oil in water with egg yolk as a binding agent. However, egg yolk and palm oil have a content that is not good for health, so other alternative ingredients are needed to make it healthier. Soybean extract and oil can replace egg yolk and palm oil as the main ingredients. Soybean extract has a "langu" aroma that not everyone likes so roasted sesame is added to reduce the aroma. This study aims to obtain the best formulation and determine the physicochemical characteristics and the level of panelists' preference for vegetarian mayonnaise. This study used a Completely Randomized Design (CRD) with roasted sesame addition factors of 0%, 10%, 20%, and 30% with three replications each. The physicochemical analysis used to determine the physicochemical content used the thermogravimetric, Soxhlet, and Kjeldahl methods, and used a viscometer and hedonic analysis to deteassess level of panelists' preference for vegetarian mayonnaise samples. The results showed that the addition of various concentrations of roasted sesame had a significant effect on the physicochemical characteristics of vegetarian mayonnaise. The water content ranges from 29.68% - 35.64%, the fat content ranges from 41.73% - 51.74%, the protein content ranges from 2.07% - 5.73%, and the viscosity level ranges from 1,684.37 MPaS - 2,045.50 MPaS. From this study, the results showed that the best formulation and the most preferred ratio of roasted sesame were at the 20% treatment level. Keywords: mayonnaise, vegetarian, soybeans, sesame, physicochemical